Protocol Evaluating the effectiveness of a school-based group programme for parents of children at risk of ADHD: the 'PArents, Teachers and CHildren WORKing Together (PATCHWORK)' cluster RCT protocol. Issue 5 (3rd September 2012) - Sayal, Kapil; Daley, David; James, Marilyn; Yang, Min; Batty, Martin J; Taylor, John A; Pass, Sarah; Sampson, Christopher James; Sellman, Edward; Valentine, Althea; Hollis, Chris
Abstract : Introduction: Early intervention for childhood behavioural problems may help improve health and educational outcomes in affected children and reduce the likelihood of developing additional difficulties. The National Institute for Health and Clinical Excellence guidelines for attention deficit/hyperactivity disorder (ADHD), a common childhood behavioural disorder, recommend a stepped care approach for the identification and management of these problems. Parents of children with high levels of hyperactivity and inattention may benefit from intervention programmes involving behavioural management and educational approaches. Such interventions may be further enhanced by providing training and feedback to teachers about the strategies discussed with parents. In relation to children with high levels of hyperactivity, impulsiveness and inattention, we aim to test the feasibility and effectiveness of a parenting programme (with and without an accompanying teacher session) in primary schools. Methods and analysis: This clustered (at the level of school) randomised controlled trial (RCT) focuses on children in their first four school years (ages 4–8 years) in the East Midlands area of England. Parents will complete a screening measure, the Strengths and Difficulties Questionnaire, to identify children with high levels of hyperactivity/inattention. Three approaches to reducing hyperactivity and attention problems will be compared: a group programme for parents (parent-only intervention); group programme for parents combined with feedback to teachers (combined intervention); and waiting list control (no intervention). Differences between arms on the short version of Conners' Parent and Teacher Rating Scales Revised will be compared and also used to inform the sample size required for a future definitive cluster RCT. A preliminary cost-effectiveness analysis will also be conducted. Ethics and dissemination: The outcomes of this study will inform policy makers about the feasibility, acceptability and effectiveness of delivering targeted behavioural interventions within a school setting. The study has received ethical approval from the University of Nottingham Medical School Ethics Committee. Trial registration: ISRCTN87634685